Fenomena Ghibah Virtual pada Komunikasi Era Milenial Menurut Perspektif Islam - Palupi Soenjoto, Wening Purbatin (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
The purpose of this study is to: 1. know the factors driving communication through social media which are non-verbal communication patterns are considered more expressive and can be kept secret without being known to many people verbally and closedly. 2. Reasons why non-verbal communication on social media is considered to have more freedom to communicate in ghibah than verbal communication. 3. Is the number of communication groups will facilitate communication emotionally and affect the formation of trust 4. Group dynamics built in communication social media groups. This research uses qualitative methods with primary and secondary data sources. Data collection techniques using observation, interviews, and documentation